2015
DOI: 10.6000/1927-7229.2015.04.04.5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the IGF Axis in Epithelial-to-Mesenchymal Transition during the Progression of Prostate Cancer

Abstract: Prostate cancer is the second most common lethal cancer in men worldwide. Despite the fact that the prognosis for patients with localized disease is good, many patients succumb to metastatic disease with the development of resistance to hormone treatments. This is normally termed castration-resistant prostate cancer (CRPC). The development of metastatic, castration-resistant prostate cancer has been associated with epithelial-to-mesenchymal transition (EMT), a process where cancer cells acquire a more mesenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 136 publications
(190 reference statements)
0
1
0
Order By: Relevance
“…This phenotypic switch results in loss of the tight cell-cell adhesion characteristic of epithelial cells and gain of a mesenchymal phenotype characterized by increased motility and invasiveness; facilitating the progression to metastatic disease. Accumulating evidence indicates a role for the insulin/IGF-axis in regulating EMT (71, 72). In relation to this epithelial plasticity two recent studies have also both reported that activation of PI3K can result in de-differentiation of lineage restricted mouse mammary epithelial cells into multipotent stem-like cells that can then differentiate into mixed lineage cells resulting in heterogeneity in subsequent tumors (73, 74).…”
Section: Cancer Mutations and Heterogeneity: A Paradigm Shiftmentioning
confidence: 99%
“…This phenotypic switch results in loss of the tight cell-cell adhesion characteristic of epithelial cells and gain of a mesenchymal phenotype characterized by increased motility and invasiveness; facilitating the progression to metastatic disease. Accumulating evidence indicates a role for the insulin/IGF-axis in regulating EMT (71, 72). In relation to this epithelial plasticity two recent studies have also both reported that activation of PI3K can result in de-differentiation of lineage restricted mouse mammary epithelial cells into multipotent stem-like cells that can then differentiate into mixed lineage cells resulting in heterogeneity in subsequent tumors (73, 74).…”
Section: Cancer Mutations and Heterogeneity: A Paradigm Shiftmentioning
confidence: 99%